TOLERANCE OF CHILDREN OLDER THAN 4 YEARS TO ACELLULAR DPT-VACCINES: RESULTS OF A RETROSPECTIVE STUDY - A. G. Gaivoronskaya; L. S. Namazova-Baranova; D. A. Novikova; M. V. Fedoseenko; N. E. Tkachenko; T. A. Kaljuzhnaya; F. Ch. Shakhtakhtinskaya; М. I. Broeva (Педиатрическая фармакология, 2017)
Background. Pertussis is a highly contagious bacterial infection of airborne transmission type that still remains a serious problem in Russia and around the world. The only reliable means of specific prophylaxis of pertussis is vaccination. In Russia, only one revaccination from pertussis is provided at the age of one and a half years, which is done with whole-cell DTP vaccine, which is not used with children older than 4 years due to high reactogenicity. Imported acellular DTP vaccines are an alternative to whole-cell  vaccines licensed for use with older children. Objective: Our aim was to study children’s tolerability of the vaccine containing acellular pertussis component. Methods.  The safety of acellular DTP vaccines (DTaP, DTaP/IPV/Hib) has been analyzed in a retrospective  study with children older than 4 years at the department of vaccinal prevention of Scientific Center of Children’s Health (Moscow) in the period from December 2014  to December  2015.Results.  The results of 123  vaccinated  children aged 4 to 9 have been studies. Among them, healthy children — 62, those having allergic disease — 30, those with other chronic diseases — 31. In the post-vaccination  period (3–7 days), local reactions (weak and/or strong) were recorded with 19 (31%) healthy children, 11 (37%) with children having allergic diseases, 9 (29%) with children having other chronic diseases. General reactions to vaccination (weak and/or strong) occurred with 11 (18%), 6 (20%), and 8 (26%) children respectively. Conclusion. The compared groups did not differ in frequency of post-vaccination  reactions and their intensity, with the exception of strong local reactions that occurred more frequently with children having allergic diseases.